If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(11 + -1x) = 2(3 + 2x) (11 * 6 + -1x * 6) = 2(3 + 2x) (66 + -6x) = 2(3 + 2x) 66 + -6x = (3 * 2 + 2x * 2) 66 + -6x = (6 + 4x) Solving 66 + -6x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 66 + -6x + -4x = 6 + 4x + -4x Combine like terms: -6x + -4x = -10x 66 + -10x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 66 + -10x = 6 + 0 66 + -10x = 6 Add '-66' to each side of the equation. 66 + -66 + -10x = 6 + -66 Combine like terms: 66 + -66 = 0 0 + -10x = 6 + -66 -10x = 6 + -66 Combine like terms: 6 + -66 = -60 -10x = -60 Divide each side by '-10'. x = 6 Simplifying x = 6
| 4x-6=-16+6x | | [378-(45*4)]/55 | | 2x+20=5x+100 | | 12=15k | | -21+7=77 | | A=2*4.6+3*1.97 | | -49m-15=69 | | 12x-72=2x-9 | | 6x-1=4x-8 | | 01+10= | | r/5=7/7 | | (2x+6)(-7x+14)=0 | | 12x=-10+70 | | X^2-4=-5x | | -11=1 | | (x+5)(x+5)=-15 | | x+5+x+125=360 | | 4x-0.8=-4 | | -x+8+3x=-6 | | 11/9=k/4 | | (X)=-2x-5 | | 12+x+3=20 | | 14x-11y=-25 | | 4(7-3x)=4 | | 40x^2+40x+1040=0 | | 12-1y/5 | | ×/4-6=-10 | | -3=-30-9r | | 18+8=1 | | 4+-4=-2+8 | | 1x-20/6 | | 9x+7y=28 |